KAJIAN KERUSAKAN LINGKUNGAN AKIBAT ALIH FUNGSI LAHAN DI DAERAH ALIRAN SUNGAI BRANTAS HULU, KOTA BATU, PROVINSI JAWA TIMUR - , Mahro Syihabuddin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of territories and population growth in the Batu city from year to year is very rapidly. This implies to the landuse exchange and environmental damage that occurs in Upper Brantas Watershed. This research aims to: 1) examines the landuse exchange based on existing condition